2019
DOI: 10.1016/j.cell.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Human Artificial Chromosomes that Bypass Centromeric DNA

Abstract: Summary Recent breakthroughs with synthetic budding yeast chromosomes expedite the creation of synthetic mammalian chromosomes and genomes. Mammals, unlike budding yeast, depend on the histone H3 variant, CENP-A, to epigenetically specify the location of the centromere—the locus essential for chromosome segregation. Prior human artificial chromosomes (HACs) required large arrays of centromeric α-satellite repeats harboring binding sites for the DNA sequence-specific binding protein, CENP-B. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 81 publications
4
95
0
Order By: Relevance
“…homolog , yet sequence features of X. laevis centromeric DNA may facilitate centromere function, as has been suggested for other species (Kasinathan and Henikoff 2018) . A recent study demonstrated that certain non-repetitive chromosomal fragments contain the ability to retain CENP-A after transient targeting of HJURP to deposit CENP-A (Logsdon et al 2019) suggesting that some non-alphoid sequences are competent for CENP-A retention. These studies challenge the notion that centromeres are specified purely by epigenetic factors and motivate the investigation of DNA sequence contributions into centromere maintenance in diverse model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…homolog , yet sequence features of X. laevis centromeric DNA may facilitate centromere function, as has been suggested for other species (Kasinathan and Henikoff 2018) . A recent study demonstrated that certain non-repetitive chromosomal fragments contain the ability to retain CENP-A after transient targeting of HJURP to deposit CENP-A (Logsdon et al 2019) suggesting that some non-alphoid sequences are competent for CENP-A retention. These studies challenge the notion that centromeres are specified purely by epigenetic factors and motivate the investigation of DNA sequence contributions into centromere maintenance in diverse model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the location of CENP-A relative to methylated DNA (specifically, 5-methylcytosines), we performed IF on stretched CHM13 chromatin fibers as previously described with modifications 82,83 . Briefly, CHM13 cells were swollen in a hypotonic buffer consisting of a 1:1:1 ratio of 75 mM KCl, 0.8% NaCitrate, and dH2O for 5 min.…”
Section: Immunofluorescence (If) and Fluorescence In Situ Hybridizatimentioning
confidence: 99%
“…HACs form in a complex and as-yet incompletely characterized process after transfection of seeding DNA into human cells. During this relatively lengthy period (typically ~3 weeks), the HAC-seeding DNA undergoes spontaneous multimerization and in at least some cases may pass through a stage when it is transiently inserted into the arm of an endogenous chromosome 3,22 . The multimerization presumably allows it to attain a threshold size required for stable chromosome segregation 23 .…”
Section: Introductionmentioning
confidence: 99%